Subjectivity of Travelers in Tere Liye's Novel Janji: Carl Thompson's Travel Literature Analysis - Darmawan, Auranita Gibrani (Politeknik Siber Cerdika Internasional, 2025)
This article uses the material object of Tere Liye's novel Janji and the formal object of Carl Thompson's depiction of the world of travel literature. This research is made to analyze the world depiction, negotiation, and ideology in the novel. Then, descriptive qualitative is used as the research method. The results of this study are (1) subjective long-distance world depiction dominates the novel Janji by Tere Liye; (2) there are three types of negotiation, namely agreement, comparison, and change. There are also three ideologies of the travelers, namely theism, humanism, and racism; and (3) based on the depiction of the world, there are negotiations and ideologies carried by the travelers.